Systematic Review : Metode dan Aplikasi Mikroenkapsulasi pada Ekstrak Bahan Alam - Muharam, Firman; Sriwidodo, Sriwidodo; Amalia, Eri (Universitas Malahayati, 2025)
ABSTRACT Natural extracts have potential in the pharmaceutical industry, cosmetics, and clinical applications because they are safe, non-toxic, and have relatively low side effects. Unfavorable taste and odor and stability problems are their disadvantages. The solution to these problems is microencapsulation technology. Microencapsulation is a technology that involves covering or coating a core substance with a polymer wall layer, resulting in micro-sized particles. The benefits of microencapsulation can protect compounds from various environmental factors such as oxidation, degradation, temperature, humidity, and light, thereby extending the shelf life of the product, improving the stability of active ingredients, preventing loss of activity, masking aromatic flavors and odors, improving the stability of volatile compounds and increasing bioavailability. The purpose of this review is to gather information about the application of microencapsulation to natural extracts and what the results of microencapsulation are. The literature review was conducted through Google Scholar and PubMed databases, and the literature selection was done using the PRISMA Flow Chart. This review results in microencapsulation technology for natural extracts made by ionic gelation, spray wet microencapsulation (SWM), solvent evaporation, freeze drying, fluid bed, and spray drying. Each method has a unique way of protecting the core substance with a polymer layer, resulting in useful microcapsules such as to reduce moisture, obtain suitable physicochemical characteristics, good flow rate, retain bioactive compounds, lower hygroscopicity, improve stability, increase shelf life, increase solubility, taste masking, maintain antioxidant content and pharmacological activity of natural ingredient extracts. This means the use of microencapsulation technology promises to improve the utilization of natural extracts in various pharmaceutical industries, cosmetics, and clinical applications. Keywords: Microencapsulation, Natural extracts, Methods, Applications ABSTRAK Ekstrak bahan alam memiliki potensi dalam industri farmasi, kosmetik dan aplikasi klinis karena aman, tidak beracun dan efek samping relative rendah. tetapi kelemahannya yaitu rasa dan bau yang tidak disukai serta masalah stabilitas. Solusi untuk masalah ini adalah teknologi mikroenkapsulasi. Mikroenkapsulasi adalah teknologi yang melibatkan penyalutan atau pelapisan zat inti oleh lapisan dinding polimer, menghasilkan partikel-partikel dengan ukuran mikro. Keunggulan mikroenkapsulasi dapat melindungi senyawa dari berbagai faktor lingkungan seperti oksidasi, degradasi, suhu, kelembaban, dan cahaya, sehingga dapat memperpanjang umur simpan produk, meningkatkan stabilitas bahan aktif, mencegah penurunan aktivitas, menutupi bau dan rasa, stabilitas dan bioavabilitas senyawa meningkat. Tujuan riview ini yaitu mengumpulkan informasi terkait aplikasi mikroenkapsulasi terhadap ekstrak bahan alam serta apa hasil dari mikroenkapsulasi tersebut. Kajian literatur dilakukan melalui database Google Scholar dan PubMed dengan seleksi literatur menggunakan Flow Diagram PRISMA. Hasil dari riview ini teknologi mikroenkapsulasi pada ekstrak bahan alam bisa dibuat dengan metode ionic gelation, spray wet microencapsulation (SWM), solvent evaporation, freeze drying, fluid bed, dan spray drying. Setiap metode memiliki cara unik dalam melindungi zat inti dengan lapisan polimer, sehingga menghasilkan mikrokapsul yang berguna seperti untuk mengurangi kelembaban, mendapatkan karakteristik fisikokimia yang sesuai, laju alir yang baik, mempertahankan senyawa bioaktif, menurunkan higroskopisitas, meningkatkan stabilitas, meningkatkan umur simpan, meningkatkan kelarutan, menutupi rasa, menjaga kandungan antioksidan dan aktivitas farmakologi ekstrak bahan alam. Penggunaan teknologi mikroenkapsulasi menjanjikan peningkatan dalam pemanfaatan ekstrak bahan alam dalam berbagai industri farmasi, kosmetik dan aplikasi klinis. Kata Kunci: Aplikasi, Ekstrak Bahan Alam, Metode, Mikroenkapsulasi.